2013
DOI: 10.1021/jz301965d
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer to Bilayer Structural Transition in Confined Pyrrolidinium-Based Ionic Liquids

Abstract: Ionic liquids can be intricately nanostructured in the bulk and at interfaces resulting from a delicate interplay between interionic and surface forces. Here we report the structuring of a series of dialkylpyrrolidinium-based ionic liquids induced by confinement. The ionic liquids containing cations with shorter alkyl chain substituents form alternating cation-anion monolayer structures on confinement to a thin film, whereas a cation with a longer alkyl chain substituent leads to bilayer formation. The crossov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
159
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(173 citation statements)
references
References 39 publications
14
159
0
Order By: Relevance
“…69 Negative temperat dence was observed for similar ILs and an Hg elec well as for molten salt electrolytes. 71 While Mo simulations, [72][73][74] modified MSA theory, 75 and DF have revealed that the DC can have both negative a temperature dependence for the restricted primitiv negative temperature dependence is expected for t and temperature of our simulations. that the use of single-frequency measurements could lead to misleading results [98][99][100] .…”
Section: B Capacitancementioning
confidence: 56%
“…69 Negative temperat dence was observed for similar ILs and an Hg elec well as for molten salt electrolytes. 71 While Mo simulations, [72][73][74] modified MSA theory, 75 and DF have revealed that the DC can have both negative a temperature dependence for the restricted primitiv negative temperature dependence is expected for t and temperature of our simulations. that the use of single-frequency measurements could lead to misleading results [98][99][100] .…”
Section: B Capacitancementioning
confidence: 56%
“…[12][13][14][15]. However, ionic liquid structure consists of alternating layers of excess cation density and excess anion density, and one squeeze-out event corresponds in fact to the squeeze-out of an electroneutral "slab" which can be considered, approximately, as two layers (one cation-and one anion-excess) together [9,[16][17][18][19][20][21][22]. In several cases of long-chain and geometrically irregular ionic liquids the squeeze-out behaviour is found to become continuous, rather than discontinuous.…”
Section: The Molecular Mechanisms Of Friction Across Ionic Liquidsmentioning
confidence: 99%
“…The influence of this structure on the lubrication properties was illuminated by comparisons made between measurements with dry and wet ionic liquids. Figure 2d,e shows measurements made with [C 10 C 1 Pyrr][NTf 2 ], which is organized in bilayers [22,24], in dry or wet conditions. A key finding of this study is that the friction coefficient for a single bilayer is independent of the water content, whereas it is enhanced by more than an order of magnitude for two bilayers when the liquid is wet.…”
Section: The Molecular Mechanisms Of Friction Across Ionic Liquidsmentioning
confidence: 99%
“…42-44 a "monolayer" to "bilayer" restructuring induced by confinement has been observed by surface forces apparatus 45 and solid-like multilayers in ionic liquids have been recently reported. 22,46 Conclusions MD simulations of ionic liquid-electrode interfaces show that a transition from a multilayer ion structure to an ordered monolayer structure can be observed at certain values of the surface charge density.…”
Section: Molecular-scale Structural Reorganizationmentioning
confidence: 99%